Law Enforcement in Building Permits on Building Planning in Kupang City is Reviewed From Kupang City Regional Regulation Number 7 Of 2015 Concerning Building - Gregorius Melianus Manggus; Aju Putrijanti (PT Publikasiku Academic Solution, 2024)
Based on the author's observations, the background of the main problem formulated is How is Law Enforcement in Building Permits in the Kupang City Area and What Factors Affect Law Enforcement on Building Procedures in the Kupang City Area? The purpose and usefulness of this study are to know and examine the effectiveness of law enforcement in Building Permits on building planning and to know and describe the inhibiting factors of law enforcement of building permits in the Kupang City Area. To answer these problems, research was carried out using the Qualitative Descriptive Analysis method by the data obtained while still paying attention to theories, principles, and legal rules, so, this research is a research sourced from primary and secondary data using an empirical juridical approach. In the results of this study, the main problem examined by the researcher explains law enforcement in building permits in the Kupang city area Regional Regulation Number 7 of 2015 concerning Building Buildings, relating to the rights and obligations violated by the operator of this building including not having a Building Permit, commensurate lines of buildings not by the provisions of the Regional Regulation, and the absence of parking facilities. By the provisions of the Regional Regulation, building operators who violate this are subject to administrative sanctions in the form of reprimands and temporary construction stoppages.